2019
DOI: 10.2967/jnumed.119.227652
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Duet of BRAF V600E and TERT Promoter Mutations Robustly Predicts Loss of Radioiodine Avidity in Recurrent Papillary Thyroid Cancer

Abstract: BRAF V600E and TERT promoter mutations, particularly their genetic duet, are well known to be associated with poor clinical outcomes of papillary thyroid cancer (PTC). Loss of radioactive iodine (RAI) avidity in recurrent PTC is a major cause of treatment failure and hence poor clinical outcomes. This study investigated the role of mutation patterns in loss of RAI avidity in recurrent PTC. Methods: This was a retrospective study of the relationship between loss of RAI avidity in structural recurrent PTC and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 22 publications
4
68
0
2
Order By: Relevance
“…A search of the TCGA-THCA database identified and characterized > 96% of driver mutations of PTC, finding BRAF (mutation in 59.7% PTC), NRAS (mutation in 8.5% PTC) and HRAS (mutation in 3.5% PTC) as the most common causative genes [33,34]. Our data are consistent with previous studies confirming that BRAF V600E gene mutation is important in the diagnosis of PTC [35][36][37]. However, BRAF also has been reported to mutate in benign thyroid nodules and is not suitable for early diagnosis of thyroid cancer [30,38,39].…”
Section: Agingsupporting
confidence: 90%
“…A search of the TCGA-THCA database identified and characterized > 96% of driver mutations of PTC, finding BRAF (mutation in 59.7% PTC), NRAS (mutation in 8.5% PTC) and HRAS (mutation in 3.5% PTC) as the most common causative genes [33,34]. Our data are consistent with previous studies confirming that BRAF V600E gene mutation is important in the diagnosis of PTC [35][36][37]. However, BRAF also has been reported to mutate in benign thyroid nodules and is not suitable for early diagnosis of thyroid cancer [30,38,39].…”
Section: Agingsupporting
confidence: 90%
“…Forty-six remaining studies were retrieved for assessment, and a flow chart showed the process of literature retrieval (Figure 1). Of 13 eligible articles, 12 were retrospective studies, and one study from China was prospective (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Two appropriate reports were included, although they were conference abstracts.…”
Section: Search Results and Characteristics Of Patientsmentioning
confidence: 99%
“…Concomitant BRAF and TERT promoter mutations worsened the survival rate of patients with PTC (10-year survival, both mutations 83% vs. wild type 99%; HR 5.62). Recently, Liu et al reported that coexisting BRAF and TERT promoter mutations are strongly associated with the loss of RAI avidity in recurrent PTC, showing a robust predictive value for failure of RAI treatment of PTC [85]. Thereafter, several studies have supported the synergistic effects of concomitant BRAF and TERT promoter mutations [78,[86][87][88].…”
Section: Tert Promoter Mutation In Thyroid Cancermentioning
confidence: 99%